Remnant cholesterol is independently asssociated with an increased risk of peripheral artery disease in type 2 diabetic patients - Song, Yi; Zhao, Ying; Bai, Xiangli; Cheng, Wenzhuo; Wang, Li; Shu, Meng; Shu, Yan; Zhang, Liyin; Jin, Si (Frontiers in Endocrinology, 2023)
Background Remnant cholesterol (RC) has been correlated with a higher risk of atherosclerosis. It has been confirmed that in the general population, an elevated RC level is related to a 5-fold higher risk of peripheral arterial disease (PAD). Diabetes is one of the strongest risk factors for PAD development. However, the association between RC and PAD in the specific population of type 2 diabetes mellitus (T2DM) has not been investigated. Herein, we investigated the correlation between RC and PAD in T2DM patients. Results The RC level in T2DM - PAD individuals was considerably greater than in T2DM - WPAD individuals (P < 0.001). RC had a positive correlation with disease severity. Further, multifactorial logistic regression analyses found that an elevated RC level was a major contributor to T2DM - PAD (P < 0.001). The area under the curve (AUC) of the RC for T2DM - PAD patients was 0.727. The cut-off value of RC was 0.64 mmol/L. Conclusion The RC level was higher in T2DM - PAD patients, and was independently linked with its severity. Diabetic patients with RC level > 0.64 mmol/L had an elevated risk of developing PAD.